SÍNTESE, CARACTERIZAÇÃO ESTRUTURAL E ESTUDO DAS PROPRIEDADES FOTOFÍSICAS E ANTITUMORAIS DE COMPLEXOS DE PtII COM PIRAZOLINAS 1,3,5- TRISUBSTITUÍDAS - Guilherme Brum Laranjeira (2022)
This work presents the study related to synthesis, structural characterization and study of the antitumor activity of three new PtII complexes based on 1,3,5-trisubstituted pyrazolines. The three new complexes were synthesized from the reaction of the K2PtCl4 complex salt, with a 1,3,5-trisubstituted pyrazoline ligand and 2,2'-bipyridine ligand, in the presence of KPF6 salt in proportions of (1:2:1: 2) respectively, in a MeOH/CH2Cl2 solvent mixture. The complexes were obtained in the form of yellowish crystals, which showed luminescence where the maximum emission peak was around 395 nm, starting from the ultraviolet region and approaching the blue region of the electromagnetic spectrum when the analyzes are performed in solution and the samples excited at 300 nm. The complete characterization of the complexes involved the techniques of X-ray diffractometry in single crystal, elemental analysis of CHN, mass spectrometry, absorption spectroscopy in the infrared region, absorption spectroscopy in the UV-Visible region and 1H, 13C and 195Pt NMR spectroscopy. Molecular orbital calculations were performed using the Time-dependent density-functional theory (TD-DFT) method to assist in the interpretation of electronic transitions observed in molecular absorption spectroscopy (UV-Vis). type MLCT (transition from metal to ligand) with IL (intraligand) and LMCT (transition from ligand to metal) with IL (intraligand). The antitumor activity of the synthesized complexes was evaluated, and it was possible to observe a superior action of the complexes when compared to the free ligands for tests carried out in situ.